Development of Modular and Adaptive Laboratory Set-Up for Neuroergonomic and Human-Robot Interaction Research - Savković, Marija; Caiazzo, Carlo; Djapan, Marko; Vukićević, Arso M.; Pušica, Miloš; Mačužić, Ivan (Frontiers in Neurorobotics, 2022)
The industry increasingly insists on academic cooperation to solve the identified problems such as workers' performance, well-being, job satisfaction, and injuries. It causes an unsafe and unpleasant working environment that directly impacts the quality of the product, workers' productivity, and effectiveness. This paper aims to give a specialized solution for tests and explore possible solutions to the given problem in neuroergonomics and human-robot interaction. The designed modular and adaptive laboratory model of the industrial assembly workstation represents the laboratory infrastructure for conducting advanced research in the field of ergonomics, neuroergonomics, and human-robot interaction. It meets the operator's anatomical, anthropometric, physiological and biomechanical characteristics. Comparing standard, ergonomic, guided and collaborative work will be possible based on workstation construction and integrated elements. These possibilities allow the industry to try, analyze and get answers for an identified problem, the condition, habits and behavior of operators in the workplace. The set-up includes a workstation with an industry work chair, a Poka-Yoke system, adequate lighting, an audio 5.0 system, containers with parts and tools, EEG devices (a cap and smartfones), an EMG device, touchscreen PC screen and collaborative robot. The first phase of the neuroergonomic study was performed according to the most common industry tasks defined as manual, monotonous and repetitive activities. Participants have a task to assemble the developed prototype model of an industrial product using prepared parts and elements, and instructed by the installed touchscreen PC. In the beginning, the participant gets all the necessary information about the experiment and gets 15 minutes of practice. After the introductory part, the EEG device is mounted and prepared for recording. The experiment starts with relaxing music for five minutes. The whole experiment lasts two sessions per 60 minutes each, with a 15 minutes break between the sessions. Based on the first experiments, it is possible to develop, construct and conduct complex experiments for industrial purposes to improve the physical, cognitive, and organizational aspects and increase workers' productivity, efficiency, and effectiveness. It has highlighted the possibility of applying modular and adaptive ergonomic research laboratory experimental set-up to transform standard workplaces into the workplaces of the future.